The Investigation of Hot Extrusion Process Parameters on Microstructure and Mechanical Performance of Aluminium Alloy in Biomedical Industry - Khalili, N.F.M. (Springer Science and Business Media Deutschland GmbH, 2021)
Aluminium alloy 7075 is chosen as the material to be investigated to replace stainless steel as the material of hyperthermic needle. Hot Direct Extrusion process is famous for reducing the size of the grain to enhance the mechanical properties of the alloy. The process parameters are investigated through several extrusion process related researches. Speed of extrusion was operated within pre-heat temperature of 350 to 450 ÂºC and pre-heat time of 1 to 2 h. The effect of extrusion parameters were analyzed by using design of experiment method including Taguchi method and Full Factorial method. Furthermore, density test, Vickers hardness test, compression test and microscopic visual inspection such as optical microscopic and scanning electron microscopic (SEM) were conducted. Several alternatives such as twist extrusion, heat treatment and aging must be done to improve the mechanical properties of extrudates. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.